Sequence coding for the alphavirus nonstructural proteins is interrupted by an opal termination codon. - Strauss, E G (1983)
We have obtained the nucleotide sequence of the genomic RNAs of two alphaviruses, Sindbis virus and Middelburg virus, over an extensive region encoding the nonstructural (replicase) proteins. In both viruses in an equivalent position an opal (UGA) termination codon punctuates a long otherwise open reading frame. The nonstructural proteins are translated as polyprotein precursors that are processed by posttranslational cleavage into four polypeptide chains; the sequence data presented here indicate that the COOH-terminal polypeptide, ns72, may be produced by read-through of this opal codon. The high degree of amino acid homology between the ns72 polypeptides of the two viruses, in contrast to the lack of conserved sequence upstream from the read-through site, suggests that ns72 plays an important role in viral replication, possibly modulating the action of other replicase components.